Analysis of the Effect of the Number of Valve Openings on the Performance Value of the Pelton Turbine Prototype - Sandra Mayang Dika Ridwan; Saputra, Alfian (Magister Teknik Mesin Universitas Pancasila, 2025)
The Pelton turbine is a type of impulse turbine that utilizes a high-pressure water jet through a nozzle to rotate the turbine buckets. One factor influencing turbine performance is the number of valve openings, as the opening size determines the water flow rate directed to the turbine. This study aims to analyze the effect of the number of valve openings on the performance of a Pelton turbine prototype. The research method employed is an experimental approach by varying the valve openings, resulting in different water flow rates, followed by measurements of torque, water power, turbine power, and efficiency. The tests were conducted under a constant load of 1 kg with 12 buckets. The results show that the maximum torque obtained was 0.2695 Nm. The highest water power of 15.41 W occurred at a flow rate of 30 LPM, while the lowest water power of 10.03 W was recorded at the smallest flow rate. The highest turbine power was 9.45 W, and the maximum efficiency was achieved at a flow rate of 26 LPM with valve openings producing an effective nozzle diameter of 9–11 mm, reaching 90.97–91.38%. The lowest efficiency was observed at a valve opening equivalent to a 9 mm nozzle diameter, at 22.15%. These findings indicate that the number of valve openings has a significant effect on Pelton turbine performance, particularly in terms of efficiency and output power